OPTIMALISASI PENDISTRIBUSIAN DAN PENDAYAGUNAAN ZAKAT DALAM MENCAPAI SUSTAINABLE DEVELOPMENT GOALS (SDGS) PADA BAZNAS KOTA SURABAYA - Asa, Restu Asa Marisza Sukma; Sri Abidah Suryaningsih (Jurnal Ekonomika dan Bisnis Islam, 2024)
Zakat worship has a dual role, namely from a religious and social perspective. From a religious perspective, zakat is the fourth pillar of Islam, while from a social perspective, zakat can provide opportunities such as improving people's welfare and alleviating poverty. Zakat is a solution to achieving economic development fairly and evenly, especially in Muslim countries if it is managed effectively and in accordance with the SDGs. This research is a descriptive qualitative research. The data and sources used are primary data and secondary data. The results of this study indicate that the implementation of zakat collected by BAZNAS Surabaya City has been distributed according to the needs of mustahik which refers to the five pillars of the BAZNAS RI program. The utilization of productive zakat in improving the economy can be felt by mustahik with the increasing income of mustahik from the business being run. Distribution and utilization have been optimal because they have increased from year to year. There are SDGs achievements, namely in the Surabaya Berdaya and Surabaya Cerdas programs. The Surabaya Berdaya program has helped alleviate poverty. BAZNAS Surabaya City supports the improvement of human resources through Surabaya Cerdas which provides education costs.